An integro-differential equation approach to study the scattering of water waves by a floating flexible porous plate. Issue 5 (3rd September 2018) - Koley, Santanu; Sahoo, Trilochan
ABSTRACT: In the present manuscript, the hydroelastic response of a flexible porous plate, floating in water of finite as well as infinite depths, is studied under the assumption of a linearized wave–structure interaction theory. Using Green's integral theorem, the associated boundary value problems are converted into integro-differential equations in terms of the plate deflection. To solve the derived integro-differential equations, the plate deflection is approximated as a superposition of the horizontal eigenfunctions in the plate-covered region. As a result, approximate explicit expressions are obtained for the physical quantities of interests such as reflection and transmission coefficients. The accuracy of the present numerical computations are analysed by comparing the results with the standard results available in the literature. It may be noted that the aforementioned physical problem is similar in nature with that of Koley et al. but the solution technique is completely different. As various results associated with the floating flexible porous plate are presented in Koley, Mondal and Sahoo (Eur. J. Mech. B- Fluid., 2018, vol. 67, 291–305) and therefore in this paper, the major emphasis is on the solution technique and only a few results are provided for comparison purpose.